Postoperative pancreatitis in biliary surgery: about 14 observations - Delgado Pereira, Bolívar; Zerbino, Víctor (Cirugía del Uruguay, 2020)
14 cases of post-operative pancreatitis in biliary surgery are analyzed. Etio-pathogeny is studied. The most important clinical characteristics and the results of post-operative controls of pancreatic enzymes in blood and uriné are emphasized. The acute hyghly lethal condition is stressed. The importance of profilaxy of this disease is· bring out, and the conservative medical treatment based specially on the of Trasylol anti-enzymes is advised.